Effects of Long Working Hours on Family Relations: Evidences of Working Women in Pakistan (Journal of Social Sciences Review, 2023)
The increasing number of women entering the workforce in Pakistan has led to changes in family dynamics and raised concerns about the effects of long working hours on family relations. This research study aims to investigate the effects of long working hours on family relations among working women in Pakistan. The present research study has also explored the specific challenges faced by working women in Pakistan due to their long working hours and how it affects their relationships with their families. This study employed a quantitative method research design. Quantitative data is collected through structured questionnaires from working women of healthcare professionals, education and the banking sector to gain a rich understanding of their experiences, challenges and coping mechanisms. A sample of 250 study participants is selected through a purposive sampling technique considering factors such as occupation, industry, and work hours. The data is analyzed through the statistical tool SPSS 26 and presented in descriptive and inferential statistics. The results of the study concluded that working women in Pakistan face significant challenges due to their long working hours. These challenges include time constraints, increased stress, and difficulty in fulfilling family obligations. The demanding nature of their work schedules often leads to work-family conflicts, which can strain relationships within the family.
Keywords: Effects; Long Working Hours; Family Relations; Working Women; Pakistan